Antropometri Pengukuran Status Gizi Balita Di Ra. Makfiratul Ilmi Bengkulu Selatan: Anthropometric Measurement of Nutritional Status of Toddlers in Ra. Makfiratul Ilmi South Bengkulu - Sari, Liya Lugita; Hilinti, Yatri; Ayudiah, Febra; Br.Situmorang, Ronalen; Herdianto, Eko (Chakra Brahmanda Lentera Institute, 2023)
Toddler period is an important period in the process of growth and development of a child. Growth includes monitoring body weight and length or height to assess the nutritional status of toddlers. The importance of monitoring the growth in children under five, the health office through the puskesmas conducts Posyandu activities for toddlers which are carried out every month. Growth monitoring is carried out because the growth and development of toddlers run simultaneously and influence each other. The method used is the measurement of the nutritional status of children under five in RA. Makfiratul Ilmi Manna Bengkulu Selatan using the anthropometric standards of body weight based on age (W/U) and body length based on age (PB/U) by WHO. After the measurements were made, the results obtained from 22 people whose nutritional status had been measured in Class A that 90% (18 people) under five had good nutrition and 10% (2 people) had more nutrition. Suggestions for this activity are for teachers and parents to pay more attention to toddler nutrition so that they can get good nutrition for toddler health.